Telaah Prinsip Good-Relationship di Dalam Kepemimpinan dan Organisasi - Zaluchu, Sonny Eli; Waruwu, Mesirawati (EDULEAD: Journal of Christian Education and Leadership, 2020)
AbstractThis research was conducted with a literature study that utilizes concepts, theories, and explanations from primary sources in books, journal papers, and other academic sources. The analysis presented descriptively to explore the principle of "good-relationship," a pattern of relationships created in leadership. The deepening of guides focuses on the efforts that need to be developed by a leader in influencing and functioning optimally for his followers to move together to achieve organizational goals. It can be concluded that transformative leadership is leadership that develops aspects of good-relationship through four main components, namely: leaders who get rid of the practice of fear, leaders who communicate effectively, leaders who are open or transparent, and leaders who are empathetic and listening. All of these components provide strong support for the formation of good-relationship patterns in any organization. Even though it can get affective commitment among followers, it was also found that these four components are an essential part of Christian leadership practice.AbstrakPenelitian ini dilakukan dengan studi literatur yang memanfaatkan konsep, teori dan penjelasan dari sumber-sumber primer berupa buku, paper jurnal dan sumber akademik lainnya. Analisis disajikan secara secara deskriptif untuk mendalami prinsip ‘good-relationship’ sebuah pola hubungan yang tercipta di dalam kepemimpinan. Pendalaman prinsip difokuskan pada usaha yang perlu dikembangkan oleh seorang pemimpin dalam memengaruhi dan berfungsi maksimal terhadap para pengikutnya untuk bergerak bersama-sama mewujudkan tujuan organisasi. Diperoleh kesimpulan bahwa kepemimpinan transformatif adalah kepemimpinan yang mengembangkan aspek good-relationship melalui empat komponen utama yakni: pemimpin yang menyingkirkan psikologi ketakutan, pemimpin yang berkomunikasi efektif, pemimpin yang bersifat terbuka atau transparan dan pemimpin yang bersifat empati dan mendengarkan. Seluruh komponen tersebut ternyata memberikan dukungan kuat bagi terbentuknya pola good-relationship di dalam organisasi manapun. Bahkan melaluinya dapat diperoleh komitmen afektif di kalangan pengikut. Juga ditemukan bahwa keempat komponen ini merupakan bagian penting di dalam praktik kepemimpinan Kristen.